Intermittent hypoxia training improves cerebral blood flow without cognitive impairment - Qihan Zhang; Qing Wang; Feiyang Jin; Dan Huang; Xunming Ji; Yuan Wang (Annals of Clinical and Translational Neurology)
Abstract Objective Brief exposure to intermittent hypoxia has been shown to potentially induce protective effects in the body. Animal studies suggest that intermittent hypoxia could increase cerebral blood flow and confer resistance to subsequent hypoxic–ischemic injury, yet clinical investigations are limited. This study aimed to evaluate the impact of a moderate short‐term intermittent hypoxia protocol on cerebral blood flow and cognitive performance. Methods Subjects who met the inclusion criteria were recruited to this study and randomized into the intermittent hypoxia group or the control group, which receives intermittent hypoxia training and sham‐intermittent hypoxia training, respectively. Cerebral hemodynamics, cognitive performance, cerebral perfusion pressure, and oxygen saturation were assessed before and after the intervention. Results A total of 100 healthy participants were included in this study. Compared to the control group, the intermittent hypoxia group exhibited higher peak systolic blood flow velocity (108.64 ± 22.53 vs. 100.21 ± 19.06, p = 0.049) and cerebrovascular conduction index (0.74 ± 0.17 vs. 0.66 ± 0.21, p = 0.027), and lower cerebrovascular resistance index (1.41 ± 0.29 vs. 1.54 ± 0.36, p = 0.044) following intermittent hypoxia training. Additionally, within‐group comparisons revealed that intermittent hypoxia training led to increased cerebral blood flow velocity, elevated cerebrovascular conductance index, and decreased cerebrovascular resistance index (p < 0.05). Other indicators including cognitive function, cerebral perfusion pressure, and oxygen saturation did not exhibit significant differences between groups. Interpretation These findings revealed that intermittent hypoxia may represent a safe and effective strategy for improving cerebral blood flow.